Clinical predictors of acute hyponatremia following LARIAT ligation of the left atrial appendage. (22nd September 2019) - Holmes, Benjamin B.; Patel, Neel; Lugo, Ricardo; Richardson, Travis; Metawee, Mohammed; Rinke, Lauren Lee; Meisch, Carol; Shoemaker, Moore Benjamin; Ellis, Christopher R.
Abstract: Introduction: Hyponatremia commonly follows percutaneous exclusion of the left atrial appendage (LAA) with the LARIAT suture delivery device. The aim of this study was to evaluate for clinical predictors hyponatremia following ligation of the appendage with the LARIAT device. Methods and Results: A retrospective analysis was conducted on 61 consecutive patients (average age 69.7 ± 9.8 years, 55.7% male) who underwent successful appendage ligation with the LARIAT device. Acute hyponatremia (AH) was defined as a drop in serum sodium (Na) by greater than or equal to 4 mmol/L within 48 hours of ligation while exaggerated acute hyponatremia (EAH) was defined as a drop greater than or equal to 10 mmol/L. Among all patients, there was a significant decrease in [Na] at 24 hours (3.26 ± 2.77 mmol/L) and 48 hours (4.98 ± 3.74 mmol/L). Thirty‐two patients (52.4%) had AH while six patients (9.8%) experienced EAH. A body mass index (BMI) of less than 28.4 kg/m 2 was associated with AH ( P = .037) while a BMI < 25 kg/m 2 was associated with EAH ( P = .021). A linear regression analysis comparing the maximum sodium decrease to the indexed left atrial (LA) diameter found that for every 1 cm/m 2 increase in indexed LA diameter, there was a 2.5 mEq/L decrease in serum sodium ( P = .04). Conclusions: Hyponatremia frequently occurs following LAA ligation with the LARIAT device. A low BMI < 25 kg/m 2 is associated with a drop in serum sodium of greater than 10 mmol/L while increasing indexed LA diameter predicts any AH. AH is also associated with a significantly lower systolic blood pressure 48 to 72 hours post LAA exclusion with the LARIAT device.